2014 37th International Convention on Information and Communication Technology, Electronics and Microelectronics (MIPRO) 2014
DOI: 10.1109/mipro.2014.6859820
|View full text |Cite
|
Sign up to set email alerts
|

Complex networks measures for differentiation between normal and shuffled Croatian texts

Abstract: This paper studies the properties of the Croatian texts via complex networks. We present network properties of normal and shuffled Croatian texts for different shuffling principles: on the sentence level and on the text level. In both experiments we preserved the vocabulary size, word and sentence frequency distributions. Additionally, in the first shuffling approach we preserved the sentence structure of the text and the number of words per sentence. Obtained results showed that degree rank distributions exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 9 publications
0
17
1
Order By: Relevance
“…In [50] our results showed that in-selectivity and out-selectivity values from shuffled texts are constantly below selectivity values calculated from normal texts. It seems that selectivity measure is able to capture typical word phrases and collocations which are lost during the shuffling procedure.…”
Section: Introductioncontrasting
confidence: 54%
See 3 more Smart Citations
“…In [50] our results showed that in-selectivity and out-selectivity values from shuffled texts are constantly below selectivity values calculated from normal texts. It seems that selectivity measure is able to capture typical word phrases and collocations which are lost during the shuffling procedure.…”
Section: Introductioncontrasting
confidence: 54%
“…We employed various methods from the LaNCoA toolkit for calculating the network measures and generating various plots in order to find the differences between two classes of networks. In [50] we extended this research by introducing additional shuffling procedure: the sentence-level shuffling procedure and by introducing a node selectivity as a new complex network measure. All shuffling procedures and network construction tasks were performed with the LaNCoA toolkit.…”
Section: The Lancoa Toolkit Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…These features position Croatian among morphologically rich and free word-order languages. So far Croatian has been quantified in a complex networks framework based on the word co-occurrences [7], [1] and compared with shuffled counterparts [8], [9].…”
Section: Introductionmentioning
confidence: 99%